Kritik Terhadap Sekularisme (Pandangan Yusuf Qardhawi) - Ismail, M. Syukri (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
Since theÂ  first appearanceÂ  untilÂ  now,Â  secularismÂ  had attractedÂ  the attention of manyÂ  people: scientists,Â  theologians, Â clergy, thinkers, and also by groups of religious studies. Due to theÂ  understandingÂ  hadÂ  containsÂ  manyÂ  irregularities,Â  especially ifÂ  this understandingÂ  entered toÂ  IslamicÂ  ideology.Â  Because secularism Â wasÂ  understoodÂ  thatÂ  was believed comeÂ  fromÂ  the Â WestÂ  not fromIslamicÂ  culture.Â  AlreadyÂ  soÂ  manyÂ  scholars, Â scientists,Â  andÂ  thinkersÂ  whoÂ  devotedÂ  criticalÂ  attentionÂ  to Â secularism,Â  one ofÂ  them wasÂ  Yusuf Qardhawi,Â  who had a very goodÂ  opinioninÂ  IslamÂ  rules,Â  heÂ  was consideredÂ  as a classicÂ  of Â scienceÂ  andÂ  aÂ  modern masterÂ  inÂ  Islam,Â  QardhawiâsÂ  criticism againstÂ  secularismÂ  based onunderstanding of Islam.Â  Based on Â theÂ  explanationÂ  above,Â  the authorsÂ  wanted to examineÂ  Yusuf Â QaradawiâsÂ  criticismÂ  againstÂ  secularism,Â  andÂ  in particular issues thatÂ  wouldbe discussed:Â  the problemsÂ  ofÂ  Qardhawiâs criticismÂ  againstÂ  secularism,Â  the reasonsÂ  ofÂ  QardhawiÂ  in criticizingÂ  secularism,Â  and theÂ  solutionÂ  that wasgiven in facing of secularism.